Предмет: Математика,
автор: карандаш28
ПОМОГИТЕ ПОЖАЛУЙСТА
Приложения:
![](https://files.topotvet.com/i/c57/c5743813ef354e7e90b8f217c72d974a.jpg)
Ответы
Автор ответа:
1
1) 5*(3a-7b) - 7*(2a-4b) = 15a - 35b - 14a + 28b = a-7b
2) 4ab(a^2-ab)-3a^2(b^2-ab) = 4a^3b - 4a^2b^2 - 3a^2b^2+3a^3b = 7a^3b - 7a^2b^2 = 7a^2b(a-b)
3) (4-b)*(b+3) = 4b-b^2 + 12 - 3b = b-b^2+12
4) (2a-3b)*(5a^2-4ab+3b^2) = 10a^3-8a^2b+6ab^2 - 15a^2b + 12ab^2 - 9b^3 = 10a^3-23a^2b +18ab^2 - 9b^3
5) (3-a)(2a+4)(a+7) = (6a-2a^2+12-4a)*(a+7) = (2a-2a^2+12)*(a+7) = 2a^2 - 2a^3 + 12a + 14a-14a^2+84 = -2a^3-12a^2+26a+84
2) 4ab(a^2-ab)-3a^2(b^2-ab) = 4a^3b - 4a^2b^2 - 3a^2b^2+3a^3b = 7a^3b - 7a^2b^2 = 7a^2b(a-b)
3) (4-b)*(b+3) = 4b-b^2 + 12 - 3b = b-b^2+12
4) (2a-3b)*(5a^2-4ab+3b^2) = 10a^3-8a^2b+6ab^2 - 15a^2b + 12ab^2 - 9b^3 = 10a^3-23a^2b +18ab^2 - 9b^3
5) (3-a)(2a+4)(a+7) = (6a-2a^2+12-4a)*(a+7) = (2a-2a^2+12)*(a+7) = 2a^2 - 2a^3 + 12a + 14a-14a^2+84 = -2a^3-12a^2+26a+84
Похожие вопросы
Предмет: Математика,
автор: dianailasova60
Предмет: Информатика,
автор: tokab6383
Предмет: История,
автор: krokodil1744
Предмет: Математика,
автор: rzevskijdenis